Incorporation of hydroxyapatite into collagen scaffolds enhances the therapeutic efficacy of rhBMP-2 in a weight-bearing femoral defect model. (December 2021) - Lackington, William A.; Gehweiler, Dominic; Zderic, Ivan; Nehrbass, Dirk; Zeiter, Stephan; González-Vázquez, Arlyng; O'Brien, Fergal J.; Stoddart, Martin J.; Thompson, Keith
Abstract: Traditional methods to promote bone healing, such as autologous bone grafting, and therapeutic strategies involving recombinant bone morphogenetic proteins (BMPs), such as BMP-2 and BMP-7, have been associated with performance limitations and dose-related safety concerns, respectively. Thus, there is an unmet need for osteoinductive bone graft substitutes that can enhance the therapeutic efficacy of rhBMP-2 and facilitate dose-reduction approaches. This study aimed to determine the therapeutic efficacy of rhBMP-2 delivered using a collagen-only scaffold (CO) (representative of clinical standards), a collagen-hydroxyapatite scaffold (CHA), and a thermoresponsive hyaluronic acid hydrogel doped with gelatin and laminin (HyA-GL). Efficacy over 14 weeks was evaluated using 2 mm segmental femoral defects in skeletally mature female F344 rats, internally fixated using a 1.25 mm-thick polyetheretherketone plate. Empty defects failed to bridge but administration of rhBMP-2 using either CO or CHA scaffolds led to successful bridging, while using HyA-GL resulted in non-union. CHA scaffolds induced enhanced and stiffer new bone formation compared to both CO and HyA-GL scaffolds. Limited luminal remodeling occurred in both CO and CHA groups. Taken together, this study has determined that a collagen-hydroxyapatite scaffold can enhance the therapeutic efficacy of rhBMP-2 compared to collagen-only scaffolds routinely used in standard clinical practice.